The makers and making of Nigerian private enterprise - Forrest, Tom (Ibadan : Spectrum Books, 1995)
The book provides a detailed, extensive account of medium and large-scale African business. It examines the growth of private enterprises in Nigeria, giving profiles of the country's key entrepreneurs. Combining ethnographic and historical perspectives, it examines the strategies and patterns of development employed by business people from the colonial period to the present day.
Includes bibliographical references (p. [279]-290) and index.
oif 10/10/14, ijb 25/02/2019
Loan
Keywords: Business enterprises; Saving and investment; Free enterprise; Private enterprises; Entrepreneurship